2016
DOI: 10.1039/c6ob01149g
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structural patterns of the antileishmanial activity of bi- and tricyclic N-heterocycles

Abstract: Influence of various structural patterns in a series of novel bi- and tricyclic N-heterocycles on the activity against Leishmania major and Leishmania panamensis has been studied and compounds that are active in the low micromolar region have been identified. Both quinolines and tetrahydrooxazinoindoles (TOI) proved to have significant antileishmanial activities, while substituted indoles were inactive. We have also showed that a chloroquine analogue induces Leishmania killing by modulating macrophage activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…We then choose to test a subclass of nitroxy compounds for their capacity to inhibit this interaction. Nitroxy compounds have recently emerged as a privileged scaffold for applications in drug discovery 15, 16 . In particular, 1,2-oxazines represent a new structural framework with significant potential for structure diversification.…”
Section: Introductionmentioning
confidence: 99%
“…We then choose to test a subclass of nitroxy compounds for their capacity to inhibit this interaction. Nitroxy compounds have recently emerged as a privileged scaffold for applications in drug discovery 15, 16 . In particular, 1,2-oxazines represent a new structural framework with significant potential for structure diversification.…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate the importance of the 1,4-dihydroquinolinic nucleus in the study of compounds with antileishmanial properties. Recent works have confirmed the interesting antileishmanial properties of quinoline derivatives (Antinarelli et al 2015;Herrera et al 2016;Navneetha et al 2017). In these works, various quinoline derivatives have been synthesized and showed results that attest to the importance of this pharmacophore nucleus for leishmanicidal activity against the promastigote form.…”
Section: Antileishmanicidal Activitiesmentioning
confidence: 81%
“…In a previous study, we identified chloroquine analog 1 as an inhibitor of L. panamensis growth in vitro ( Herrera et al., 2016 ). Herein, we developed a simple model of L. panamensis infection in mice to evaluate the in vivo effect of this and other compounds with a suspected antileishmanial effect.…”
Section: Resultsmentioning
confidence: 99%
“…Its chemical scaffold is used in the design of many pharmacologically-active synthetic compounds ( Kouznetsov et al., 2005 ). In a previous study, we observed that the chloroquine analog N 4 -(7-chloro-2-cyclohexanylquinolin-4-yl)- N 1 , N 1 -diethylpentane-1,4-diamine (here called compound 1 ) inhibited the growth of L. panamensis amastigotes in vitro with a half maximal inhibitory concentration (IC 50 ) of 1.07 ± 0.51 μM and with the concomitant inhibition of the production of IL-10 by infected murine macrophages ( Herrera et al., 2016 ). Here, we studied the in vivo effect of this compound on a murine model of L. panamensis infection.…”
Section: Introductionmentioning
confidence: 99%